Nano-fibrin stabilized CaSO4 crystals incorporated injectable chitin composite hydrogel for enhanced angiogenesis & osteogenesis. (20th April 2016) - Arun Kumar, R.; Sivashanmugam, A.; Deepthi, S.; Bumgardner, Joel D.; Nair, Shantikumar V.; Jayakumar, R.
Highlights: The prepared chitin–CaSO4 –nFibrin injectable gel showed osteoangiogenic properties. nFibrin addition transformed the CaSO4 crystal shape from needle to hexagonal. Composite gel showed high elastic modulus and complex strain percentage. nFibrin masked the retarding effect of CaSO4 towards in vitro angiogenesis. Early osteogenesis was observed in presence of composite gel. Abstract: Calcium sulfate (CaSO4 ), an excellent biodegradable bone forming agent that is an ideal choice as additive in gels, however, its disadvantage being poor gel rheology and angiogenesis. Here, we have synthesized chitin–CaSO4 –nano-fibrin based injectable gel system which shows improved rheology and angiogenic potential. Rheological studies showed that the composite gel was a shear thinning gel with elastic modulus of 15.4 ± 0.275 kPa; a 1.67 fold increase over chitin control. SEM and XRD analyses revealed the effect of nano-fibrin (nFibrin) in transforming CaSO4 crystal shape from needle to hexagonal. It also masked the retarding effect of CaSO4 towards in vitro early cell attachment and angiogenesis using rabbit adipose derived mesenchymal stem cells (rASCs) and HUVECs, respectively. rASCs osteogenesis was confirmed by spectrophotometric endpoint assay, which showed 6-fold early increase in alkaline phosphatase levels and immuno-cytochemistry analysis. These in vitro results highlight the potential of injectable chitin–CaSO4 –nFibrin gel for osteo-regeneration via enhanced angiogenesis.